(untitled) (Innovative professional education, 2023)
In order to successfully employ graduates and develop their entrepreneurial skills, career development centers are effectively functioning on the basis of professional (vocational and technical) education institutions of Luhansk Oblast and Ukraine as a whole. They will help young people find their first job, as well as adapt their knowledge and skills to the needs of the labor market. The centers have become assistants to graduates not only in finding their future job, but also help them prepare for the start of their career path. The materials of this article demonstrate regional activity in this direction, reveal certain achievements and some problems in individual components.